Analysis of a level-crossing experiment on the 2 P3 state of He3 - Hinds,EA; Prestage,JD; Pichanick,FMJ (Physical Review A, 1986)
We have used the theory presented by us in a recent paper to analyze a 1967 level-crossing experiment on the 2 P3 state of He3 performed at the University of Michigan. Until now a consistent analysis of the experiment had not been possible because of inadequate development of the theory. The present analysis gives excellent agreement with the results of an atomic beam magnetic resonance experiment performed recently by us at Yale University. In fact we have used the combined data to give slightly improved results for four of the 11 relevant parameters. These four are the spin-antisymmetric contact hyperfine interaction constant [C'=-4327(69) MHz)], the 2 P3 dipole hyperfine interaction constant [D=-28.145(21) MHz], the 2 P3 tensor hyperfine interaction constant [E=-7.1353(38) MHz], and the orbital g factor [gL=0.999 828 6(20)].. AE © 1986 The American Physical Society.